Orders and Sequences in the Acquisition of L2 Morphosyntax, 40 Years On: An Introduction to the Special Issue. Issue 1 (March 2015) - Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> This Special Issue of Language Learning provides a state‐of‐the‐art overview of current perspectives on acquisition orders and sequences in second language acquisition. It contains examples of empirical studies, theoretical reflections of, and a dialogue between proponents of Dynamic Systems Theory, Learner Varieties, Processibility Theory, Processing Determinism, Sociocultural Theory, and Usage‐Based Linguistics. This introduction presents the context and rationale for the collection of contributions.